A Collaborative Usability Evaluation (CUE) Model for Health IT Design and Implementation. Issue 4 (3rd April 2017) - Hundt, Ann Schoofs; Adams, Jean A.; Carayon, Pascale
ABSTRACT: In this article, the authors describe a collaborative usability evaluation (CUE) model based on a participatory ergonomics framework. The model was applied to an organization's health IT design and implementation processes. Individuals received education on usability evaluation principles and methods and had an opportunity for hands-on experience with usability testing. Actual usability evaluations increased participant confidence in their ability to independently design and lead such evaluations. The CUE model has since been applied to the organization's iterative process of health IT design, has been institutionalized by the health IT department, and is integrated in its health IT implementation timelines.